Antifungal Activity of Alchornea cordifolia and Ficus exasperata Leaves Against Trichophyton mentagrophyte and Trichophyton verrucosum (Nigerian Journal of Pharmaceutical Research, 2024)
Background: The use of plant based natural products as alternative remedy for mycosis has gained global prominence, hence the need to explore the antifungal potentials of readily available herbs.Aim: To compare the antifungal activity of the ethanol leaf extracts of Alchornea cordifolia and Ficus exasperata against Trichophyton mentagrophyte and Trichophyton verrucosum with that of conventional griseofulvin.Method: Plant samples were extracted with ethanol via maceration. Phytochemical screening was carried out using standard techniques. The ethanol extract of the fresh and dried leaves of Ficus exasperata and Alchornea cordifolia were compared with griseofulvin (0.03mg/ml) for activity against Trichophyton mentagrophyte and Trichophyton verrucosum using agar well diffusion method at varying concentrations.  Results: Both crude drugs contains flavonoids, saponins, tannins, and cardiac glycosides. Ficus exasperata extracts also contains phlobatannin and terpene. The extracts exhibited a dose dependent fungal inhibition. The highest concentration (150mg/ml) of A. cordifolia and F. exasperata extracts exerted the highest zones of inhibition (16.7mm, 19.3mm, and 19.00mm, 19.7mm, respectively) against T. mentagrophyte. The zones of inhibition of the test drugs against T. verrucosum were 20mm, 19.3mm, and 21.3mm, 24.7mm, respectively. The least mean zone of inhibition was observed at 25mg/ml. Minimum inhibitory concentration (MIC) of 50mg/ml was obtained for Alchornea cordifolia fresh and dried leaves and Ficus exasperata dried leaves while minimum inhibitory concentration of 25mg/ml was obtained for the Ficus exasperata (fresh) leaves.Conclusion: These results clearly elucidates the potentials of fresh and dry extracts of A. cordifolia and F. exasperata as a good source of antifungal compounds.
Keywords: Ficus exasperata; Alchornea cordifolia; Antifungal; Extract